Adsorption Behaviors of Different Water Structures on the Fluorapatite (001) Surface: A DFT Study - Cui, Weiyong; Song, Xueli; Chen, Jianhua; Chen, Ye; Li, Yuqiong; Zhao, Cuihua (Frontiers in Materials, 2020)
To investigate the effect of hydration behavior on fluorapatite structure, single H2O molecule as well as three layers cluster adsorptions on the fluorapatite (001) surface were performed by means of density functional theory. Results show that single H2O molecule can form stable chemisorption structures with fluorapatite (001) surface in the form of single-site, two-site and three-site adsorption, and the corresponding adsorption energies are 64.817kJ/mol, 98.712 kJ/mol and 139.620 kJ/mol, respectively. Ca2+ can bind with the O of the H2O molecule in the form of ionic interaction, which are mainly contributed by O2p and Ca 3d states, and the interacting length is close to the Ca—O bond in the bulk fluorapatite. Adsorption configuration of three layers of water molecules on fluorapatite (001) surface shows serious hydration reconstruction at the interface, these atoms in the surface layer are highly distorted and the Ca and the PO4 groups are shifted in opposite directions in the z-axis direction.